Automated IT Processes; Architectural design proposal for supporting automated IT processes in a Microsoft environment - Melberg, Marcus; Westerström, Markus (My University, 2009)
This master thesis defines and evaluates a system architecture proposal that will support automated IT processes systems in a Microsoft environment. The architecture is based upon programming models in the .NET framework and will enable systems to be integrated with Microsoft’s Identity Lifecycle Manager (ILM). It is intended to be adaptable to changes and provide strength to the integration of the different programming models. The architecture has been evaluated by a prototype that has been built using Windows Presentation Foundation and Windows Communication Foundation. Windows Workflow Foundation has also been used to define workflows that are hosted by ILM. The result is an architectural design that provides scalability and a separation of concerns. The architecture can be seen as a structural framework that provides stability for further development. The prototype can be seen as the realization of this architecture, with features and functionalities that are common in applications for automated IT processes. The most important question that this thesis aimed to answer; is it possible to use the .NET framework and ILM to build applications for automated IT processes, was answered by the result of the prototype. ILM constrains the infrastructure and the architecture but provides strength to important attributes such as maintainability and extendibility. The combination of ILM and the .NET programming models in this master thesis has been proven successful for automated IT processes.
Keywords: Programvaruteknik; Software Engineering